2021
DOI: 10.1080/24740527.2021.1889925
|View full text |Cite
|
Sign up to set email alerts
|

Attending work with chronic pain is associated with higher levels of psychosocial stress

Abstract: Background and Aims : Much is known about the impact of pain in terms of medical costs and missed work. Less is known about its associations when individuals are present for work. This study examines “presenteeism” by analyzing the psychosocial costs of pain in the workplace, using the 2015 European Working Conditions Survey (EWCS). Methods : We conducted cross-sectional analysis of 2384 individuals with chronic pain and 2263 individuals without pain (matched by age and sex) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Second, the questions about the percent chance of working full-time past ages 62 and 65 do not specifically measure retirement expectations. In fact, the questions may also capture intentions to transition to part-time work, which would be consistent with previous research finding that workers with pain are more likely to engage in part-time work ( Adams & Salomons, 2021 ). However, because older workers’ most common response to new health-related work limitations is to stop working ( Schimmel Hyde et al, 2022 ), we argue that our findings speak to expectations about retirement among individuals with physically demanding jobs who experience pain.…”
Section: Discussionsupporting
confidence: 84%
“…Second, the questions about the percent chance of working full-time past ages 62 and 65 do not specifically measure retirement expectations. In fact, the questions may also capture intentions to transition to part-time work, which would be consistent with previous research finding that workers with pain are more likely to engage in part-time work ( Adams & Salomons, 2021 ). However, because older workers’ most common response to new health-related work limitations is to stop working ( Schimmel Hyde et al, 2022 ), we argue that our findings speak to expectations about retirement among individuals with physically demanding jobs who experience pain.…”
Section: Discussionsupporting
confidence: 84%
“…Studies demonstrating the negative or positive consequences of sick leave have previously been called for [38]. In a study from 2021, Adams et al found that employees attending work and suffering from chronic pain experience higher levels of psychosocial stress than those without pain [39]. Although the majority of the participants in our study managed to stay in work and believed it helped them to for cope, they might also experience increased pain and higher level of psychosocial distress which could influence their recovery from heel pain.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty percent of the respondents were employed, 34.4% were unemployed and only 15.6% were self-employed. A study suggested that when someone from a workplace experiences pain, it may lead to loss of productivity due to absenteeism (Adams, 2021). In addition, one tends to have lesser income due to inability to work as a consequence of pain.…”
Section: Methodsmentioning
confidence: 99%